Changes in diaphragm contractility in cigarette smoking‐exposed and smoking cessation rats are associated with alterations in mitochondrial morphology and homeostasis. Issue 5 (20th August 2022) - Zhang, Yijie; Shi, Xiaoqian; Sheng, Haiyan; Hu, Yuhan; Pang, Baosen; Ma, Yingmin; Jin, Jiawei
Abstract: The effects of cigarette smoking (CS) cessation on the diaphragm are unknown, as are the CS‐induced diaphragmatic mitochondrial changes. We examined the changes in diaphragm contractility, as well as alterations in mitochondrial morphology, function and homoeostasis during CS exposure and after cessation. Rats were randomly divided into CS exposure and CS cessation groups: 3‐month CS (S3), 6‐month CS (S6), 6‐month CS followed by 3‐month cessation (S6N3). The changes in the diaphragm were investigated, including contractile properties, the ultrastructure, mitochondrial function and the expression of markers of mitochondrial homoeostasis. CS caused irreversible histological disruption and functional depression in the lungs, along with significantly declines in diaphragmatic contractility and more severely in extensor digitorum longus muscular contractility. Such declines were recovered after 3‐month CS cessation. CS exposure disrupted the diaphragmatic mitochondrial morphology and function (S6), which was significantly alleviated in the S6N3 group. The mitochondrial homoeostasis was depressed (S6), as indicated by the downregulation of Pink1 and Mfn1. Interestingly, the Mfn1 level was recovered after smoking cessation (S6N3). In conclusion, smoking cessation eased CS‐induced diaphragmatic dysfunction and mitochondrial deregulation, which are likely associated with deregulated mitochondrial homoeostasis.